Estudo, an?lise e proposta de uma arquitetura de integra??o de sistemas heterog?neos em redes de larga escala com adapta??o de uma plataforma de suporte a agentes m?veis - FT-SALE / SMAM - Silva, Cristiane Moreira da (2006)
A Virtual Enterprise is a temporary alliance of enterprises that come together to share skills or core competencies and resources in order to better respond to business opportunities, and whose cooperation is supported by computer networks. In this dissertation, it is presented an integration proposal of two platforms that work in the context of Virtual Enterprises: the Partners Search and Selection Platform, developed to explore the benefits of mobile agents paradigm, that allows more agility on the partners search and selection process during these enterprises implementation, and the FT-SALE Platform, whose proposal is to adequate the FTCORBA failure tolerant techniques to the Virtual Enterprise environment. Thus, the main advantage of this merge is to use the failure tolerant techniques to improve reliability on Virtual Enterprise partner and selection process. Besides this, the insertion of a mobile multi-agent system in the context of the FT-SALE Platform opens other opportunities that can be explored on future works. Therefore, the main motivation for his work was to improve failure detection and membership control management on Partners Search and Selection Platform, offering more reliability for Virtual Enterprise formation and objects communication. Thus, this dissertation presents and discuss the main technologies behind these platforms as well as proposes a new platform called FT-SALE/SMAM Platform. At the end, they are presented guidelines for its implementation.